Improving the Delivery and Replication of Oncolytic Viruses - Roy, Dominic (Université d'Ottawa / University of Ottawa, 2016)
The optimal route for clinical delivery of oncolytic viruses (OVs) is thought to be intravenous (IV) injection; however, the immune system is armed with several highly efficient mechanisms to remove pathogens from the circulatory system. To overcome the challenges in trying to deliver OVs IV, cell carriers have been investigated to determine their suitability as delivery vehicles for systemic administration of OVs. Here we demonstrate the utility of a Drosophila melanogaster cell platform for the production and in vivo delivery of multi-gene biotherapeutic systems. We show that cultured Drosophila S2 cell carriers can stably propagate OV therapeutics that are highly cytotoxic for mammalian cancer cells without adverse effects on insect cell viability or cellular gene expression. Drosophila cell carriers administered systemically to immunocompetent animals trafficked to tumours to deliver multiple biotherapeutics with little apparent off-target tissue homing or toxicity, resulting in a therapeutic effect. S2 cells provide a genetically tractable platform supporting the integration of complex, multi-gene biotherapies while avoiding many of the barriers to systemic administration of mammalian cell carriers. Once OVs are delivered to tumour beds, they initiate replication in tumour cells, which often possess defects in antiviral pathways and are thus susceptible to infection. However, not all tumours have defects in their antiviral defenses and thus virus replication in these tumours is rather limited. Identifying and modulating host factors that regulate virus replication in OV-resistant cancer cells, but not normal cells, could lead to increased replication in these tumours and potentially improve therapeutic outcomes. We therefore conducted an RNA interference screen using Sindbis virus (SINV) in order to identify host factors that modulate OV replication in tumour cells. Specifically, serial passage of a SINV- artificial microRNA (amiRNA) library in a tumour cell line followed by deep sequencing of ii the selected virus populations led to the identification of several amiRNA sequences that were enriched. Furthermore, the identified amiRNA sequences increased the replication of various OVs both in vitro and in vivo, ultimately resulting in an enhanced therapeutic effect. Overall, the work presented here highlights strategies in which both the systemic delivery and tumour-specific replication of OVs can be improved.
Keywords: cancer; oncolytic virus; delivery; RNAi